Patriotic information systems - Loendorf, Todd.; Garson, G. David. (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2008)
"This book discusses how, with its non-participatory enforcement ethos, its inherent bias against freedom of information, and its massive claims on IT budget resources, the information technology security system of the future may be even less hospitable to the democratic visions which some theorists once anticipated would be among the most important contributions of information technology to society"--Provided by publisher.